EVALUATION OF NUTRITIONAL EFFECTS AND DIGESTIVE BALANCE OF THREE CASSAVA-DISHES COMMONLY CONSUMED IN CÔTE D'IVOIRE AT WISTAR RATS - Hermann, Yéboué Kouamé; Ernest, Amoikon Kouakou; Joël, Kouamé Konan; Alexendre, Zoho Bi Foua Guy; Estelle, Essé Sonia (International Journal of Research -GRANTHAALAYAH, 2018)
Valuing local dishes can help eradicate undernourishment in west Africa. In this context, the aim of this study is to evaluate in wistar rat nutritional effects and digestive balance of attiéké, attoukpou and placali, three cassava-dishes, commonly consumed in Côte d'Ivoire. For this purpose, 5 diets were composed to conduct growth and digestive balance experiments in wistar rats. Staple foods of the five diets are cassava-based foods (attiéké, attoukpou and placali), potatoes starch and sucrose. Four diets contain 45% of starch from different foods (attiéké, attoukpou, placali and potato). The last diet is starch-free, and contains sucrose as source of carbohydrate. This study showed that, cassava based-diets (attiéké, attoukpou and placali) have resulted in very good growth of rats, the efficiency of these foods is better, starch of cassava dishes has a digestibility greater than 95%. However, because of the difference in culinary treatments, nutritional performance of attiéké is reduced compared to attoukpou and placali. Cassava-based foods, mainly attoukpou and placali, favored protein utilization in rat growth. Diets based on potato starch and sucrose have the lowest feed efficiency and a very low growth performance in rats. Consumption of Cassava dishes may therefore dampen undernourishment.